Waifs and Strays: Property Rights in Late Medieval England. (January 2022) - Claridge, Jordan; Gibbs, Spike
Abstract: This article provides new insights into long-standing debates on lord-tenant relations in medieval England and how they were negotiated through the manorial court. We examine an institution, which we term the stray system, that facilitated cooperation between lords and tenants to manage stray livestock. Specifically, we argue that the stray system is a clear example of a public good. In this context, the system was a social benefit provided by lords to their tenants as a collective. In a world where most of the population was dependent on agriculture for their livelihoods, any potential damage to a crop would have been of real concern. However, in managing the threat of wandering livestock, the property rights of owners had to be clearly protected to avoid disputes over ownership. The manorial court's management of strays provided an institution to resolve these countervailing pressures. Ultimately, that system helped to protect a community's arable land—the most vital source of income for lords and tenants alike—while simultaneously assuring the property rights of those who had lost important capital assets in the form of livestock.